Influence of Particle Size Distribution on Mechanical Behavior of Hydrate-bearing Sands - Zafar, Raheel (Schulich School of Engineering, 2021)
Gas hydrates are natural ice-like, crystalline solid compounds that form in both permafrost and deep-water oceanic sediments. The large volumes of methane gas stored in hydrates make them an ideal resource for the world’s future energy demands. Hydrate-bearing coarse-grained sand sediments have great potential for commercial exploitation due to their high permeability and high hydrate content within pore space. The formation of hydrates significantly increases the strength and stiffness of host sediment and their dissociation directly impact host sediment stability. A recent study on natural hydrate-bearing sediments reported a significant correlation between sediment particle size and its strength and stiffness. Therefore, to ensure sustainable gas production activities, the effect of sediment particle size on the large-strain mechanical response of hydrate-bearing coarse-grained sediments needs to be investigated. This thesis reports on an experimental program that allowed the controlled and homogenous formation of gas hydrates within laboratory synthesized sand specimens and their subsequent laboratory testing to investigate the effect of particle size on their mechanical response. Specimens containing a different proportion of large particle sizes were prepared and their mechanical properties were investigated in two states: base sand (BS) and hydrate-bearing sand (HBS). Results show that the hydrate growth rate appears to be dependent on the particle size of sediment, with a decrease in sand particle size increasing the hydrate growth rate. Triaxial test results show that the strength and stiffness of HBS specimens strongly depend on particle size, hydrate saturation, and applied effective stress. The influence of particle size becomes evident at high hydrate saturations (> 46%). Increasing the proportion of large particles within the sediment matrix significantly increases the strength and stiffness of HBS specimens. The cohesion also exhibits dependency on particle size. An increase in the specific ...